2016
DOI: 10.5539/jgg.v8n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Implications of Hydrologic Regime Change in Chongwe River, Zambia

Abstract: Conflicts regarding water use have emerged in some small irrigation dominated peri-urban catchments in Zambia; Chongwe being one such catchment. Despite these conflicts suggesting a change in hydrologic regime, the nature of the changes and their drivers has not been adequately investigated. The Mann Kendall trend test and Flow Duration Curves were used to investigate changes in hydro-climatic time series data in Chongwe upper catchment for the period . Although the results reviewed a significant upward trend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…The observed trend for a period of 34 years shows that precipitation is decreasing at a rate of 0.12 Mm 3 /year. This decrease agrees with the findings in the study by Chisola et al [28] in which the decrease was attributed to climate change.…”
Section: Hydrological Water Balance For Chongwe River Catchment and Isupporting
confidence: 93%
See 1 more Smart Citation
“…The observed trend for a period of 34 years shows that precipitation is decreasing at a rate of 0.12 Mm 3 /year. This decrease agrees with the findings in the study by Chisola et al [28] in which the decrease was attributed to climate change.…”
Section: Hydrological Water Balance For Chongwe River Catchment and Isupporting
confidence: 93%
“…This is in line with the result that showed there is high runoff in rainy seasons and very low in dry period. The study conducted by Chisola et al [28] on the upper catchment of the Chongwe River also indicated that there is an increase in runoff during wet season flows and a reduction in dry season flows. An analysis of the long-term time series variation of streamflow at the outlet of the catchment for a period of 34 years (Figure 7) indicates that the streamflow is increasing at a rate of about 0.13 Mm 3 per annum.…”
Section: Hydrological Water Balance For Chongwe River Catchment and Imentioning
confidence: 92%
“…The Chongwe River Catchment (shown in Figure 1) largely covers the Chongwe district of Lusaka province in Zambia. The catchment also covers the districts of Lusaka, Chibombo, Kafue, and a small fraction of the Luangwa district [10]. It is a sub-catchment of the Zambezi Catchment and covers a total area of 5150 km 2 .…”
Section: Study Areamentioning
confidence: 99%
“…Various studies have been conducted by other researchers in this regard. Chisola & Kuraz [10] investigated the patterns and implications of hydrologic regime change in the upper Chongwe River Catchment and reported that human activities in the upstream region of the catchment could be the major contributing factors to the changes in flow regime.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation